Architecture as a determinant in shaping the identity of a city: A case study of Almaty - Gulnarа Abdrassilova; Laura Aukhadiyeva (Urbani Izziv)

(untitled)
This article identifies the determinants contributing to the configuration of a city’s identity. It presents the outcomes of a study on modes of expressing identity, exemplified through the case of Almaty, Kazakhstan’s largest urban conurbation. Based on a public opinion analysis, a set of factors is identified that contributes to shaping Almaty’s city identity. The findings indicate that modern architecture is important for preserving and expressing the identity of the city and region, which, in turn, is a source of investment and tourism interest in a particular area. Globalization, more than ever before, accentuates the challenge of searching for and preserving the identity of cities and regions. The importance of studying identity problems lies in the fact that the findings can be used to develop strategies for sociocultural and economic transformations of a city.